Barriers to breast self-examination practice among female undergraduate students in Universiti Sains Malaysia - Asri, Nurul Izzah (Pusat Pengajian Sains Kesihatan, 2022)
Breast cancer is a very common cancer in women. Breast cancer is a cancer that forms in the cells of the breasts. It most often begins with cells in the milk-producing ducts (invasive ductal carcinoma). Breast cancer is a common cancer which gives risk to one out of 19 women aged between 30 and 60 years in Malaysia. As an effective methods for early breast cancer detection, mammography, clinical breast examination (CBE) and breast self- examination (BSE). Although BSE are the most suitable screening for breast cancer, there has been some debate over the accuracy of detecting breast cancer. Therefore, this study was conducted to identify the possible barriers and preventive measures of these barriers among undergraduate student in School of Health Sciences, USM. A cross-sectional study was conducted in Universiti Sains Malaysia (USM) from October 2021 until July 2022. A total of 84 respondents was purposively selected and the data was collected using a structured self-administered questionnaire. The mean age of the respondents was 23 years old (SD= 1.02), with age ranging between 21 to 28 years old. Pearson’s Chi-Square or Independent T- test was used to determine the association of selected sociodemographic factors and barriers toward performing BSE to the prevalence of BSE practice. Results showed that the prevalence of practicing BSE was 81.0% and majority perform BSE at the age more than 20 years old. The results also showed that most of the respondents had a moderate level of barrier (51.2%). There is no statistically significant association between the prevalence rate of BSE practice and barriers of BSE practice. The study also revealed there was no statistically significant association between the age, family history of breast cancer and exposure to breast disease with the prevalence of BSE practice. As conclusion, the level of barrier among undergraduate students were moderate and the prevalence of BSE practice is high. The barriers toward performing BSE should be evaluate and recognized to allow early prevention interventions to decrease the prevalence of breast cancer and its complication.